Methodology for the Formation of Creative Competence of Future Teachers in the Process of Teaching Mathematics based on a Special Complex of Tasks - Dilfuza Melievna, Makhmudova (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of developing a methodology for creating the creative competence of future teachers in the process of teaching mathematics based on special tasks. The article discusses the implementation of components of creativity in conditions such as: didactic - the allocation in the target component of mathematics education of the goals of forming the creative competence of future teachers, the use of methods and forms of teaching mathematics aimed at creating the creative competence of future teachers, the sequential complication of types of creative activity; organizational and methodological - the implementation of differentiated teaching of mathematics, the use of life experience of students in the educational process, building up the subject-subject relations between all participants in the educational process - the conditions for teaching mathematics to future teachers contributes to the formation of their creative competence. The article defines the main criteria for the level of formation of creative competence of future teachers: motivational, cognitive, active, reflective; levels of formation: low, medium, high. A special complex of creatively-oriented mathematical tasks has been developed that meets the requirements of problematicity, focusing on students to gain new knowledge and gaining experience in conscious inclusion in creative activity, non-determinism of the student’s actions when completing the task, the significance of the result for the student, the orientation of the tasks to form one or more components creative competency is a means of forming and developing a creative competency of future teachers in teaching mathematics.